Effects of arsenic exposure on lipid metabolism: a systematic review and meta-analysis. (24th March 2021) - Zhao, Yannan; Li, Meng; Tian, Xiaolin; Xie, Jiaxin; Liu, Penghui; Ying, Xiaodong; Wang, Meng; Yuan, Jiyu; Gao, Yi; Tian, Fengjie; Yan, Xiaoyan
Abstract: Lipid metabolism dysfunction is a risk factor for cardiovascular diseases. Reportedly, arsenic exposure could affect lipid metabolism, but this finding remains controversial. Herein, we updated and reevaluated evidence regarding the relationship between arsenic exposure and lipid metabolism. Electronic and manual searches were performed to determine the effect of arsenic exposure on lipid metabolism from inception up to 30 November 2019. Overall, five studies were included in our meta-analysis. Two reviewers independently extracted information. Standardized mean difference (SMD) and 95% confidence intervals (CI) were used to analyze the combined effects of four indicators related to lipid metabolism (total cholesterol [TC], triglyceride [TG], high-density lipoprotein [HDL], low-density lipoprotein [LDL]). Afterwards, subgroup and sensitivity analyses were performed to explore the source of heterogeneity. Publication bias was tested using funnel plots and Begg's test. In this study, we observed that arsenic exposure can affect lipid metabolism by reducing serum HDL levels and increasing serum LDL levels. Following subgroup analysis, the arsenic concentration appeared to affect lipid metabolism. Funnel plot and Begg's test suggested no asymmetry. In conclusion, we recommend that potential influencing factors, including age, exposure time, and multiple concentration gradients, should be considered to further explore the relationship between arsenic exposure and lipid metabolism.